Using Online Support Communities for Tourette Syndrome and Tic Disorders: Online Survey of Users' Experiences - Perkins, Victoria; Coulson, Neil S; Davies, E Bethan (JMIR Publications, 2020)
BackgroundPeople living with a tic disorder (TD)-such as Tourette syndrome (TS)-experience many negative psychological and social challenges arising from chronic tics, such as stigmatization from peers and poorer quality of life, and these can impact upon their families too. It can be difficult for this population to access face-to-face support for tics, and so online support communities offer one avenue for support from peers facing similar experiences. However, little is known about how online support communities may be used by people with TS and other TDs, and by others (eg, parents, caregivers) supporting a person with TS/TD. ObjectiveThis study aimed to explore users' experiences of participation in online support communities for TS and TDs. MethodsIn total, 90 respondents (aged 13-62 years; 62% [56/90] female) from 13 countries completed an online survey exploring their experiences of using online support communities for TS and TDs. Respondents were people living with TS/TD themselves (n=68) or supportive others of someone with TS/TD (eg, parent, sibling, spouse; n=14), or both (n=8). The online survey contained open-ended questions eliciting their self-reported motivations for using online communities, their benefits and drawbacks of participation, and whether online support communities affected offline management of tics. Responses were analyzed using thematic analysis. ResultsSeven overarching themes captured experiences of using online support communities for TS/TDs. The overwhelming reason for their use was to find accessible support due to a lack of offline face-to-face support. Online support communities were valued sources of informational and emotional support, and also had a positive impact upon helping users' psychological well-being. Online communities helped provide a space where people with TS/TDs could feel accepted and reduce the social isolation they felt offline. The suggestible nature of tics and being reminded of the challenging nature of TDs were main disadvantages arising from using online support communities, alongside conflict arising within online communities. ConclusionsThe findings suggest that online support communities appear to offer valuable informational and emotional support to those living with TS/TD and their families too, especially given the lack of locally available support. This facilitates a sense of community online, which can help users in overcoming long-standing social isolation and aid self-reported improvements in psychosocial well-being. Users reported some drawbacks in engaging with online support communities, such as conflict between different types of users and triggering content, which negatively affected experiences of community participation.